Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-94519-4
|View full text |Cite
|
Sign up to set email alerts
|

Movement kinematics and cortical activation in children with and without autism spectrum disorder during sway synchrony tasks: an fNIRS study

Abstract: Children with Autism Spectrum Disorder (ASD) have difficulties with socially embedded movements such as imitation and interpersonal synchrony (IPS); however, related movement characteristics and underlying neural mechanisms are not well understood. This study compared the movement characteristics and cortical activation patterns of children with and without ASD during a whole-body, sway synchrony task when different levels of social information were provided. Thirty children with and without ASD (mean age: 12.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Most studies focused on imitation and synchrony-based cooperative actions but not turn-taking or competition. Using fNIRS and motion tracking systems, we have reported differences in behavioral performance and cortical activation in healthy adults and school-age children with and without an ASC during multiple interpersonal synchrony tasks involving reaching/body sway versus solo actions 25 28 . In this study, we extend our past work to a novel naturalistic, dyadic building game using Lincoln Logs in children with and without an ASC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies focused on imitation and synchrony-based cooperative actions but not turn-taking or competition. Using fNIRS and motion tracking systems, we have reported differences in behavioral performance and cortical activation in healthy adults and school-age children with and without an ASC during multiple interpersonal synchrony tasks involving reaching/body sway versus solo actions 25 28 . In this study, we extend our past work to a novel naturalistic, dyadic building game using Lincoln Logs in children with and without an ASC.…”
Section: Discussionmentioning
confidence: 99%
“…Most fMRI studies have investigated ASC-related cortical activation when the participants imitated/followed others finger/hand motions and reported atypical activation over OEMS regions 16 , 17 . Using fNIRS, our research group has also reported hypoactivation in the IFG and STS regions along with hyperactivation in the IPL region when children with an ASC engaged in synchronous reaching or whole-body sway motions while following the lead of an adult partner 27 , 28 . Although activation differences between leading and turn-taking joint actions are not well-studied; studies have found reduced prefrontal activation in individuals with an ASC during executive functioning tasks requiring inhibition control and motor planning 43 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using fNIRS, our research group has reported differences in cortical activation in infants at-risk for and children with ASD during socially embedded actions (i.e., actions performed with adults and caregivers), solo movements, and action observation compared to healthy children and adults during social interaction as well as interpersonal synchrony tasks involving reaching and whole-body movements (67)(68)(69)(70)(71)(72). We have consistently found lower fNIRS activation in the superior temporal sulcus and middle/inferior frontal gyri in infants at-risk for and children with ASD compared to controls (67)(68)(69)(70)(71)(72). In certain tasks involving synchronous reaching and body sway, fNIRS activation was associated with ASD severity and communication performance (69,71).…”
Section: Implications and Recommendation For Future Researchmentioning
confidence: 99%
“…EEG abnormalities associated with arousal/motivation, inhibitory control, and mental flexibility tasks have also been reported in individuals with ASD, ADHD, and/or LD (64)(65)(66). Using fNIRS, atypical fronto-parieto-temporal activation has been reported in infants at risk for and children with ASD during naturalistic, socially embedded actions compared to age-matched controls (67)(68)(69)(70)(71)(72). It would be reasonable to expect that physical activity/movement interventions that are known to have cascading effects on psychosocial and cognitive performance may also lead to associated changes in neural activity in the aforementioned neural correlates/biomarkers.…”
Section: Introductionmentioning
confidence: 99%